Olive Cake Meal and Bacillus licheniformis Impacted the Growth Performance, Muscle Fatty Acid Content, and Health Status of Broiler Chickens - Ahmed A. Saleh (Animals, 2020)
Olive cake meal (OCM) is characterized by its high nutritional value and is used as an alternative source of protein and fats in poultry diets. However, due to the high percentage of fiber in OCM, beneficial bacteria cells are used to improve the digestion rates. Therefore, the influence of OCM and Bacillus licheniformis (BL) on the growth, nutrient utilization, blood chemistry, and muscle fatty acid profile of broilers was exclusively examined in this study. Three hundred and sixty birds were randomly divided into six experimental groups (6 replicates/10 birds each): Control, OCM (2%), OCM (4%), BL, OCM (2%)/BL, and OCM (4%)/BL groups. Although feed intake was not meaningfully influenced by dietary treatments, weight gain was enhanced and feed conversion ratio was reduced (p < 0.05). The abdominal fat was lowered in broilers fed OCM (2%), OCM (4%), OCM (2%)/BL, and OCM (4%)/BL diets without a difference to those fed BL only (p < 0.05). Interestingly, blood total protein, albumin, Newcastle disease (ND) titer, and high-density lipoprotein (HDL) cholesterol were significantly increased, while total cholesterol was decreased by the mixture of OCM and BL (p < 0.05). Muscle oleic and linoleic acids, as well as vitamin E, increased significantly in broilers fed both OCM (4%) and BL, while linolenic acid increased in all groups except those fed BL and control diets (p < 0.05). Liver malondialdehyde (MDA) was decreased by feeding BL or both OCM at 2% or 4% and BL (p < 0.05). In conclusion, the inclusion of BL to OCM diets resulted in improved fat utilization and, accordingly, enhanced growth, nutrient utilization, and antioxidative response in broilers. Based on the obtained results, it is recommended to use BL to improve the nutritional value of OCM and to increase the feed utilization of OCM by broilers.